The lioness of Boston - Franklin, Emily (2023)
"By the time Isabella Stewart Gardner opened her Italian palazzo-style home as a museum in 1903 to showcase her collection of old masters, antiques, and objects d'art, she was already well-known for scandalizing Boston's polite society. But when Isabella first arrives in Boston in 1861, she is twenty years old, newly married to a wealthy trader, and unsure of herself. Puzzled by the frosty reception she receives from stuffy bluebloods, she strives to fit in. After two devastating tragedies and rejection from upper-society, Isabella discovers her spirit and casts off expectations." -- Book jacket.
Includes bibliographical references.
Keywords: Gardner, Isabella Stewart, -- 1840-1924 -- Fiction; Art -- Collectors and collecting -- Fiction; Boston (Mass.) -- Fiction; Biographical fiction